1975
DOI: 10.1017/s0033291700056403
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric symptom profiles of patients with epilepsy: a controlled investigation

Abstract: SynopsisA comparison was made of the mental state of patients with chronic epilepsy and matched controls with locomotor disorders, using a reliable psychiatric interview technique. The symptom profiles of the two groups were similar. The profiles of temporal lobe and other epileptics were also similar. Epileptic patients with a high current psychiatric morbidity were characterized by a raised incidence of previous neurotic illness and raised neuroticism scores on the Eysenck Personality Inventory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(62 citation statements)
references
References 18 publications
3
58
1
Order By: Relevance
“…One of the reasons the depressed epileptics had high N scores is because the EPI is sensitive to depression. This would also complement the findings of Standage and Fenton (1975) who found higher N and lower E scores in a group of psychiatrically impaired epileptics compared with a control group of epileptics from a neurolog,J clinic.…”
Section: The Eysenck Personality Inventorysupporting
confidence: 75%
See 3 more Smart Citations
“…One of the reasons the depressed epileptics had high N scores is because the EPI is sensitive to depression. This would also complement the findings of Standage and Fenton (1975) who found higher N and lower E scores in a group of psychiatrically impaired epileptics compared with a control group of epileptics from a neurolog,J clinic.…”
Section: The Eysenck Personality Inventorysupporting
confidence: 75%
“…He found a significant association between a 500/o reduction in seizure frequency before admission to hospital in patients admitted with depressive illness, while an increase in seizure frequency was common in those epileptic patients admitted with either acute behaviour disturbance or clouded states. Standage and Fenton (1975) in their study found that epileptics scored higher on various items including somatic symptoms of depression and depressive mood. They found that, in addition, a significantly higher proportion of the "high scoring" group had experienced fewer attacks than usual in the month before examination.…”
Section: 2ii L~ter-ictal Depressionmentioning
confidence: 91%
See 2 more Smart Citations
“…Furthermore, Kanner and Palac (2000) have emphasized the clinical significance of this epilepsy-specific mood disorder, demonstrating that at least three quarters of epilepsy patients with depressive symptoms have non-clinical depression according to the Diagnostic and Statistical Manual of Mental Disorders Fourth Edition (DSM-IV) criteria, and that anhedonia without sadness or irritability may predominate. However, others refute the idea of an epilepsy-specific mood disorder and suggest that depressive symptoms in epilepsy are similar to those seen in patients without epilepsy ( Standage and Fenton 1975;Dodrill and Batzel 1986;Metcalfe et al 1988;Reilly et al 2006). Overall, the prevailing idea is that the constellation of depressive symptoms in patients with epilepsy mostly overlaps with that observed among patients with idiopathic major depression (Lambert and Robertson 1999).…”
Section: Introductionmentioning
confidence: 99%